Penggunaan Formula Mineral Lokal dalam Ransum Ayam Petelur - Khalil Khalil (Faculty of Animal Science, Bogor Agricultural University, 2010)
A mineral formula composed of three locally available materials: limestone originated from Bukit Kamang of West Sumatra, freshwater oyster shell and bone meal and fortified with micro minerals of Cu, Zn and I was investigated as mineral supplement for diet of laying hens. The experimental diets were: P0 (diet contained of 6% commercial mineral), P1 (diet contained of 6% local mineral), P2 (diet contained of 6% Bukit Kamangs' limestone) and P3 (diet contained of 6% fresh water oyster shell meal). The total of four experimental diets was then fed to 120 laying hens. The hens were divided into 3 groups based on body weight: heavy, medium and light. Each group was subdivided into 4 subgroups in accordance with number of treatments, so that each treatment consisted of 3 replicates containing of 10 hens. Parameters measured included: feed intake, hen-day egg production, feed conversion ratio (FCR), eggshell quality, mineral retention and mineral composition of tibia bone. Data were subjected to statistical analysis using variance analysis in a completely block design with 4 treatments and 3 blocks as replicates The results showed that the egg weight and eggshell qualities were found not significantly difference, but different mineral sources gave significant effect on egg production and bone mineralization. The laying performances and tibia bone weight of chickens fed diet mixed with the local mineral formula were found not significantly different with those fed diet mixed with commercial formula, but significantly better (P < 0.05) than those of fed diet mixed with only limestone or oyster shell. Hens fed with diet mixed with Bukit Kamangs' limestone showed better performances and heavier tibia bone than those fed with diet mixed with oyster shell. It was concluded that the local mineral formula could be used as sole mineral source for laying hens. The nutritive value of Bukit Kamangs' limestone was better than that of fresh water oyster shell.